PENGEMBANGAN KURIKULUM AHMADIYAH DI SMA PIRI YOGYAKARTA - Takrip, Muhamad (Edudeena : Journal of Islamic Religious Education, 2018)
Abstract: The Ahmadiyya movement born in the 19th century with the background of the decline of Muslim India in the field of religious, political, economic, social and other areas of life. The Ahmadiyya movement has a controversy among Muslims in Indonesia from various walks of life with the advent of the Ahmadiyya in Indonesia education need for qualitative scientific research that could explain that the Ahmadiyya in high school education PIRI Yogyakarta with Ahmadiyya islam education learning more emphasis towards the understanding of contextual and good nature substance through belief in God as well as the attitude towards fellow humanbeings. In Indonesia has many tribal differences, religion, race and the education of Ahmadiyya appreciate differences is an attempt religious teachers in multicultural education in high school imparts PIRI. Abstrak: Gerakan Ahmadiyah lahir pada abad ke 19 dengan latar belakang kemunduran umat islam India dibidang agama, politik, ekonomi, sosial dan bidang kehidupan lainya. Gerakan Ahmadiyah memiliki kontroversi di kalangan umat islam Indonesia dari berbagai kalangan dengan munculnya pendidikan Ahmadiyah di Indonesia perlu adanya penelitian ilmiah secara kualitatif yang bisa menjelaskan bahwa pendidikan Ahmadiyah di SMA PIRI Yogyakarta dengan pembelajaran pendidikan agama islam Ahmadiyah lebih mengedepankan terhadap pemahaman kontekstual dan subtansi baik sifatnya keyakinan kepada Allah maupun sikap terhadap sesama manusia. Di Indonesia memilki banyak perbedaan suku, agama, Ras dan antargolongan pendidikan Ahmadiyah menghargai perbedaan merupakan upaya guru agama dalam menanamkan penddikan mutikultural di SMA PIRI Yogyakarta.